A simple route to functionalize siloxane polymers for DMMP sensing. Issue 6 (24th July 2013) - Wang, Yang; Du, Xiaosong; Li, Yi; Long, Yin; Qiu, Dong; Tai, Huiling; Tang, Xianzhong; Jiang, Yadong
ABSTRACT Hexafluoroisopropanol (HFIP) was the most widely used functional group for nerve agents detection. However, to incorporate HFIP group into a polymer backbone, highly toxic hexafluoroacetone gas was needed in a conventional synthetic route. In this article, a new route with low toxicity was proposed to synthesize a strong hydrogen‐bond acidic (HBA) siloxane polymer by using 2‐vinylhexfluoroisopropanol as the raw material in the hydrosilylation reaction. The synthesized fluoroalcoholic linear polysiloxane (LSFA) was characterized by FT‐IR, confirming its molecular structure was much similar to SXFA, a well‐established HBA polymer synthesized by the conventional route. TGA data verified the adduct's thermal stability. The dimethyl methylphosphonate (DMMP) sensing properties of LSFA and SXFA, along with PLF, were compared basing on the surface acoustic wave (SAW) platform. The results demonstrated that the conventional synthetic route was somewhat difficult to handle and control, while the new route was simpler, easier and was an effective and promising alternative. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 4516–4520, 2013